Design of protective headgear for soccer players through experimental and computational analysis - Hassan, Mohd Hasnun Arif (2019)
The uniqueness of soccer is the fact that one is allowed to use the head to direct the ball in the game. This purposeful ball-to-head impact has become one of the causes of head injuries in soccer. Clinical studies have linked multiple soccer headings with the risk of sustaining mild traumatic brain injury. This study attempts to look into this matter from the engineering perspective. A human head finite element model was adopted from a previous study and validated against a published cadaveric experimental data of intracranial pressures and linear head acceleration. A good agreement was reached between the predicted head responses and those of the cadaveric experiment. The validated soccer ball and human head finite element models were assembled to perform soccer heading simulations. To validate the finite element analysis, a soccer heading experiment was conducted on human volunteers. An instrumented mouthpiece was used to record linear and angular head accelerations during the soccer heading trials. The simulation results match those of the experiment with more than 80% accuracy. Furthermore, the study aims to evaluate the efficacy of impact-absorbing foams in mitigating the risk of sustaining head injury due to soccer heading. Another soccer heading experiment was carried out with the volunteers wearing a commercial soccer headgear. The linear and angular head accelerations obtained were compared to those of without wearing the headgear. The results demonstrate that the headgear is incapable of reducing the risk of head injury. Finite element analyses of soccer heading with wearing the headgear were performed. The comparison of both results reveal a good agreement, which suggest that the finite element models developed is a useful tool in the development of a new protective headgear for soccer players. In addition, parametric studies of the foam material properties show that an elastomeric foam alone might not be able to attenuate the risk of sustaining head injury due to soccer heading.